Effect of short-term light irradiation with varying energy densities on the activities of nitrifiers in wastewater. (1st June 2022) - Yang, Mingzhu; Qiu, Shuang; Wang, Lingfeng; Chen, Zhipeng; Hu, Yanbing; Guo, Jianhua; Ge, Shijian
Highlights: Effects of light irradiation on the activities of nitrifiers were investigated. Irradiation power affects nitrifiers more over irradiation time and sludge concentration. Light irradiation with appropriate energy densities stimulates AOB activity. Photostimulation might be related to enhanced electronic transport and energy utilization. Metabolic disorders and lipid peroxidation probably contribute to photoinhibition. Abstract: Microalgal-bacterial consortium (MBC) process has been proposed as an alternative to conventional activated sludge process for nitrogen removal from wastewater. As one of the most influencing parameters, light irradiation effects on microalgae have been extensively investigated. However, light influence on the performance of nitrifiers in activated sludge and its mechanism remains unclear. In this study, the effects of three factors (light irradiation power, irradiation time and sludge concentration) on activities and physiological characteristics of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) were systematically studied through both the Design of Experiments driven response surface methodology (RSM) approach and light-nitrification kinetic modeling. Results indicated that light irradiation with the specific light energy density ( Es ) at 0.0203–0.1571 kJ·mg −1 VSS (80–160 W/400–1000 μmol·m −2 ·s −1, 2.0–5.0 h and 2750–4250 mg·L −1 ) stimulated the relative AOB activities ( rAOB ) by 120.0%. This was supported by the increased electron transport system activity, key enzyme activity (AMO), gene expression ( amoA ) and energy generation (ATP consumption) in the light treatment. Moreover, further Es increasing up to 0.18 kJ·mg −1 VSS inhibited both AOB and NOB activities. The inhibition was ascribed to the joint light responses of metabolic disorders and lipid peroxidation. The findings enhance our understanding of nitrifiers' physiological responses to short-term light irradiation, and promote the development of MBC as a sustainable approach for wastewater treatment. Graphical abstract: Image, graphical abstract